Association of depression with mortality in an elderly treated hypertensive population - Chowdhury, E.; Berk, M.; Nelson, M.; Wing, L.; Reid, Christopher (Cambridge University Press, 2018)
Background:Both elevated blood pressure and/or depression increase the risk of cardiovascular disease and mortality. This study in treated elderly hypertensive patients explored the incidence of depression, its association (pre-existing and incident) with mortality and predictors of incident depression.Methods:Data from 6,083 hypertensive patients aged =65 years enrolled in the Second Australian National Blood Pressure study were used. Participants were followed for a median of 10.8 years (including 4.1 years in-trial) and classified into: "no depression," "pre-existing" and "incident" depression groups based on either being "diagnosed with depressive disorders" and/or "treated with an anti-depressant drug" at baseline or during in-trial period. Further, we redefined "depression" restricted to presence of both conditions for sensitivity analyses. For the current study, end-points were all-cause and any cardiovascular mortality.Results:313 (5%) participants had pre-existing depression and a further 916 (15%) participants developed depression during the trial period (incidence 4% per annum). Increased (hazard-ratio, 95% confidence-interval) all-cause mortality was observed among those with either pre-existing (1.23, 1.01-1.50; p = 0.03) or incident (1.26, 1.12-1.41; p < 0.001) depression compared to those without. For cardiovascular mortality, a 24% increased risk (1.24, 1.05-1.47; p = 0.01) was observed among those with incident depression. The sensitivity analyses, using the restricted depression definition showed similar associations. Incident depression was associated with being female, aged =75 years, being an active smoker at study entry, and developing new diabetes during the study period.Conclusions:This elderly cohort had a high incidence of depression irrespective of their randomised antihypertensive regimen. Both pre-existing and incident depression were associated with increased mortality.